Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada Pt. Bank Rakyat Indonesia Unit Sibolangit - Napitupulu, Arahandson; Haryati, Endang (Jouska: Jurnal Ilmiah Psikologi, 2024)
This study aims to empirically examine how the influence of service quality on customer satisfaction at PT. Bank Rakyat Indonesia Sibolangit Unit. The type of research used in this study is a quantitative approach. The sampling technique in this study uses purposive sampling. The population in this study is 1,800 loan customers of PT Bank BRI Sibolangit Unit in the last 2 years The data analyst method used in this study is partial analysis. The service quality scale is compiled based on the aspect of service quality. In measuring customer satisfaction based on the aspect of Customer Satisfaction. Based on the results of the partial analysis calculation, it can be seen that there is an influence on service quality with customer satisfaction. This result is evidenced by the correlation coefficient rxy = 0.994, with a significant p = 0.000 0.05. The determinant coefficient (R2) of the influence between the independent variable and the bound variable is R2= 0.988. This shows that the quality of service is distributed by 98.80% to customer satisfaction.